Kinerja usaha Kuritos berbasis balanced scorecard di Kabupaten Kaur Provinsi Bengkulu - Salsa Bila; Gita Mulyasari; Irnad; Ellys Yuliarti (COMPOSITE : Jurnal Ilmu Pertanian, 2026)
Kaur Regency has significant potential for octopus resources, with production reaching 276,031 kg per year, encouraging the development of processing-based enterprises, including IKM Putra Daerah, which produces octopus crackers under the brand “Kuritos.” However, high availability of raw materials does not necessarily translate into optimal business performance. Theoretically, the Balanced Scorecard emphasizes that business performance should be achieved by balancing financial and non-financial aspects. In reality, the Kuritos business demonstrates relatively good financial performance but still faces limitations in production capacity and employee productivity, resulting in suboptimal overall performance. This gap between the ideal condition and the actual situation forms the basis of this study. This research aims to analyze Kuritos' business performance across financial and non-financial dimensions using the Balanced Scorecard approach. The study employs a case study design with a qualitative descriptive approach supported by quantitative data. The results indicate that financial performance is considered good, with an R/C ratio of 1.20 and a break-even point already achieved; however, business profits remain relatively low relative to the regional minimum wage. In terms of non-financial aspects, customer and employee satisfaction are relatively high, but production volume and employee productivity have not yet reached the expected targets. Overall, business performance is categorized as moderate, with a score of 0.6, indicating a need to strengthen production capacity and marketing strategies to sustainably improve performance.